Standardization of Flow Cytometric Immunophenotyping for Hematological Malignancies: The FranceFlow Group Experience. Issue 9 (31st July 2019) - Solly, Françoise; Angelot‐Delettre, Fanny; Ticchioni, Michel; Geneviève, Franck; Rambaud, Hubert; Baseggio, Lucile; Plesa, Adriana; Debliquis, Agathe; Garnache‐Ottou, Francine; Roggy, Anne; Campos, Lydia; Aanei, Carmen; et al.
Abstract: Flow cytometry is broadly used for the identification, characterization, and monitoring of hematological malignancies. However, the use of clinical flow cytometry is restricted by its lack of reproducibility across multiple centers. Since 2006, the EuroFlow consortium has been developing a standardized procedure detailing the whole process from instrument settings to data analysis. The FranceFlow group was created in 2010 with the intention to educate participating centers in France about the standardized instrument setting protocol (SOP) developed by the EuroFlow consortium and to organise several rounds of quality controls (QCs) in order to evaluate the feasibility of its application and its results. Here, we report the 5 year experience of the FranceFlow group and the results of the seven QCs of 23 instruments, involving up to 19 centers, in France and in Belgium. The FranceFlow group demonstrates that both the distribution and applicability of the SOP have been successful. Intercenter reproducibility was evaluated using both normal and pathological blood samples. Coefficients of variation (CVs) across the centers were <7% for the percentages of cell subsets and <30% for the median fluorescence intensities (MFIs) of the markers tested. Intracenter reproducibility provided similar results with CVs of <3% for the percentages of the majority of cell subsets, and CVs of <20% for the MFI values for the majority of markers. Altogether, the FranceFlow group show that the 19 participating labs might be considered as one unique laboratory with 23 identical flow cytometers able to reproduce identical results. Therefore, SOP significantly improves reproducibility of clinical flow in hematology and opens new avenues by providing a robust companion diagnostic tool for clinical trials in hematology. © 2019 International Society for Advancement of Cytometry Abstract :